2011
DOI: 10.1007/s00442-011-2218-3
|View full text |Cite
|
Sign up to set email alerts
|

Detecting predators and locating competitors while foraging: an experimental study of a medium-sized herbivore in an African savanna

Abstract: Vigilance allows individuals to escape from predators, but it also reduces time for other activities which determine fitness, in particular resource acquisition. The principles determining how prey trade time between the detection of predators and food acquisition are not fully understood, particularly in herbivores because of many potential confounding factors (such as group size), and the ability of these animals to be vigilant while handling food. We designed a fertilization experiment to manipulate the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
83
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 68 publications
8
83
0
1
Order By: Relevance
“…Carrying out multiple tasks simultaneously can reduce an animal's attention and efficiency with respect to predator detection (Dukas, 2002), and researchers have suggested that vigilance while handling food would reduce the chance of detecting a predator because of the noise resulting from the mastication process (Blanchard & Fritz, 2007;Fortin et al, 2004;. The investment of social foragers in these two types of vigilance has been shown to vary with predation risk, food resource characteristics, group size and the distance between foragers (Benhaim et al, 2008;Fern andez-Juricic, Beauchamp, & Bastain, 2007;Meer et al, 2012;Pays et al, 2012;.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Carrying out multiple tasks simultaneously can reduce an animal's attention and efficiency with respect to predator detection (Dukas, 2002), and researchers have suggested that vigilance while handling food would reduce the chance of detecting a predator because of the noise resulting from the mastication process (Blanchard & Fritz, 2007;Fortin et al, 2004;. The investment of social foragers in these two types of vigilance has been shown to vary with predation risk, food resource characteristics, group size and the distance between foragers (Benhaim et al, 2008;Fern andez-Juricic, Beauchamp, & Bastain, 2007;Meer et al, 2012;Pays et al, 2012;.…”
mentioning
confidence: 96%
“…handling or chewing) its food (hereafter termed 'vigilance with chewing') (e.g. Lima, Zollner, & Bednekoff, 1999;Meer, Pays, & Fritz, 2012;Pays et al, 2012;Robinson & Merrill, 2013). However, while differing in terms of their costs to foraging, these two types of vigilance may also differ in the quality of perception that they offer .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…We argue that the level of provisioning and attraction for wildlife species in some systems may reduce seasonal variations in activity budgets of impala social groups. Observations made by Pays et al [15] indicate that improving forage patch quality modifies the trade-offs between vigilance and foraging in favour of feeding. Animals invest time in the acquisition of information about forage resources within their environmental setting thus affecting the proportion of time allocated to other activities [16].…”
Section: Introductionmentioning
confidence: 99%
“…A partir de um olhar etológico, podemos olhar a agressão como um comportamento social, mesmo sendo este agonístico. Ao compartilhar um mesmo ambiente com outros indivíduos da mesma espécie se obtém benefícios como a cooperação ativa com outros, ganhos na localização de alimento e diminuição do risco de predação (Bijleveld, van Gils, Jouta & Piersma, 2015;Josephs, Bonnell, Dostie, Barrett, Henzi, 2016;Pays et al, 2012). Mas na mesma medida a convivência em grupo implica custos como a disseminação de doenças, maior visibilidade aos predadores e o surgimento da competição pelos recursos (Altizer et al, 2003;Aureli & de Waal, 2000 (Simon & Lu, 2005;Waltes, Chiocchetti & Freitag, 2015).…”
Section: Qual é a Causa Filogenética Da Agressão?unclassified